2015
DOI: 10.1152/jn.00298.2015
|View full text |Cite
|
Sign up to set email alerts
|

Direct-effects and after-effects of visuomotor adaptation with one arm on subsequent performance with the other arm

Abstract: Adapting to a novel sensorimotor condition is generally thought to result in the formation of an internal representation associated with the novel sensorimotor transform. While the presence of after-effects following sensorimotor adaptation is taken as evidence that such an internal representation was developed as a result of adaptation, it remains unclear whether the absence of after-effects following sensorimotor adaptation indicates that no internal representation was developed. In the present study, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…In the study by Wang and colleagues [ 7 ] significant intermanual transfer was observed when participants reached with their untrained hand when was a cursor was presented. Thus, perhaps implicit processes play a greater role in intermanual transfer if participants have the opportunity to see the cursor during transfer (i.e., direct-effects are assessed and not aftereffects; see [ 11 ]), as in the task of Wang et al [ 7 ], and implicit contributions are not dissociated from explicit contributions to visuomotor adaptation as in the current study. With respect to the size of the visuomotor distortion, we had participants adapt to a 40° visuomotor distortion, while Wang et al [ 7 ] had participants adapt to a 32° distortion.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the study by Wang and colleagues [ 7 ] significant intermanual transfer was observed when participants reached with their untrained hand when was a cursor was presented. Thus, perhaps implicit processes play a greater role in intermanual transfer if participants have the opportunity to see the cursor during transfer (i.e., direct-effects are assessed and not aftereffects; see [ 11 ]), as in the task of Wang et al [ 7 ], and implicit contributions are not dissociated from explicit contributions to visuomotor adaptation as in the current study. With respect to the size of the visuomotor distortion, we had participants adapt to a 40° visuomotor distortion, while Wang et al [ 7 ] had participants adapt to a 32° distortion.…”
Section: Discussionmentioning
confidence: 87%
“…Initial findings led to the proposal that intermanual transfer of visuomotor adaption arises because the underlying processes are effector independent [see 11 ]. Specifically, both hands have shared access to a sensorimotor map that has been updated implicitly (i.e., unconsciously) through error-based motor learning, such that motor commands have been adapted to minimize the difference between predicated and actual sensory feedback experienced [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further insight about these mechanisms that mediate learning and the nature of the resulting motor memories can be obtained by examining how it generalizes to unpracticed conditions, a principle that in fact applies to multiple learning systems such as the declarative (Alvarez and Squire 1994) and perceptual (Yotsumoto et al 2009) systems. Some studies on motor memory generalization have revealed that the memories developed via motor adaptation comprise of both effector-dependent and effector-independent components (Wang and Lei 2015; Wang et al 2015). Effector-independence has been surmised from the finding that learning with one effector often generalizes to another, untrained effector.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of visual and proprioceptive manipulation during training introduced significantly higher performance gains in the non-trained hand relative to other existing training types such as learning by observation 17 , and CE 3 with and without passive hand movements 24 25 26 .…”
Section: Discussionmentioning
confidence: 88%
“…In learning by observation, it has been demonstrated that significant performance gains can be obtained simply by passively observing someone else perform the task 16 17 18 19 20 . Similarly, proprioceptive training, in which the limb is passively moved, was also shown to improve performance on motor tasks 12 21 22 23 24 25 26 .…”
Section: Introductionmentioning
confidence: 96%